2016
DOI: 10.1007/s00586-016-4384-9
|View full text |Cite
|
Sign up to set email alerts
|

Double-level degenerative spondylolisthesis: what is different in the sagittal plane?

Abstract: Multi_DS have different sagittal alignment than single DS with greater PI. In multi_DS, malalignment is more important with larger anterior tilt, loss of lumbosacral lordosis and more compensatory mechanisms such as pelvic retroversion. These findings highlight the need for an adapted surgical correction in these older patients with greater sagittal malalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…In this study, 77.6% of double-level DLS patients were women, which is similar to that obtained by previous studies [18,19]. Previous studies have shown that compared with single-level DLS, women with double-level DLS account for a larger proportion (approximately 70%) [14]. Interestingly, this study found that women in the anterior type accounted for a larger proportion of women in double-level DLS, while men and women had a similar proportion in the combined type group.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, 77.6% of double-level DLS patients were women, which is similar to that obtained by previous studies [18,19]. Previous studies have shown that compared with single-level DLS, women with double-level DLS account for a larger proportion (approximately 70%) [14]. Interestingly, this study found that women in the anterior type accounted for a larger proportion of women in double-level DLS, while men and women had a similar proportion in the combined type group.…”
Section: Discussionsupporting
confidence: 90%
“…The most common level of slippage in single-level DLS patients is L4L5, but the levels of L3L4-L4L5 and L4L5-L5S1 is common in double-level DLS patients [14]. This study found that L3L4-L4L5 and L4L5-L5S1 levels of spondylolisthesis are common in double-level DLS, which is similar to that obtained in previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations